2020
DOI: 10.3389/fpubh.2020.00237
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Disease Burden Attributable to Tobacco in China, 1990–2017: Findings From the Global Burden of Disease Study 2017

Abstract: In 2018, there were more than 371 million cigarette smokers and 12. 6 million electronic cigarette users, with 340.2 million non-smokers exposed to secondhand smoke (SHS) in China, which resulted in heavy tobacco-attributable disease burden. According to the definition by the Global Burden of Disease Study 2017 (GBD 2017), tobacco is a level 2 risk factor that consists of three sublevel risk factors, namely, smoking, SHS, and chewing tobacco. In this study, we aimed to evaluate the trends in deaths and disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…For the demographic variables, we find that being male, older (until a certain age), divorced, and having an education level below university degree, low household income, and low household assets are related to the current smoking status. Our results are consistent with those of previous studies, which found that smoking is more prevalent and progressive in males [e.g., ( 13 , 73 78 )] and persons in lower socioeconomic status (SES) [e.g., ( 73 , 79 85 )]. A plausible explanation is that persons in higher SES groups tend to have more knowledge about health risks and better access to health care resources and smoking cessation services ( 79 , 84 ), which results in a lower rate of smoking prevalence compared to those in the lower SES group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For the demographic variables, we find that being male, older (until a certain age), divorced, and having an education level below university degree, low household income, and low household assets are related to the current smoking status. Our results are consistent with those of previous studies, which found that smoking is more prevalent and progressive in males [e.g., ( 13 , 73 78 )] and persons in lower socioeconomic status (SES) [e.g., ( 73 , 79 85 )]. A plausible explanation is that persons in higher SES groups tend to have more knowledge about health risks and better access to health care resources and smoking cessation services ( 79 , 84 ), which results in a lower rate of smoking prevalence compared to those in the lower SES group.…”
Section: Discussionsupporting
confidence: 93%
“…Smoking has substantially negative health [e.g., ( 7 13 )], behavioral [e.g., ( 14 16 )], and economic consequences [e.g., ( 17 , 18 )]. One important question is why do many people still engage in smoking despite its harmful effects.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that the prevalence of tobacco use among adults has decreased in recent years, but tobacco consumption among teenagers and young adults tends to remain high (Jayawardhana et al, 2019). Another study, which was conducted in China and focused on the effect of smoking-related diseases, showed a significant decrease in the prevalence of smoking observed from 1990 to 2017 in both males and females, while confirming the long lagged effect of smoking and deaths, as the smoking-related death rates showed an increasing trend in both sexes during the study period (Wen et al, 2020). In general, smoking remains a major public health concern, as it is a leading cause of death and morbidity in almost every country (Ng et al, 2014;Braillon, 2017).…”
Section: • 1 Introduction and Theoretical Backgroundmentioning
confidence: 82%
“…But there is a new phenomenon called e-cigarette smoking; the study of Azagba et al, (2020) showed that the use of electronic cigarettes among young people increased significantly from 2014 to 2018. For example, in 2018 in China, there were more than 371 million cigarette smokers and 12.6 million electronic cigarette users (Wen et al, 2020). Electronic cigarettes may have offset conventional smoking among adolescents and young adults by maintaining the total prevalence of nicotine use and diverting them from more harmful conventional smoking.…”
Section: • 1 Introduction and Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation